Survey of Recently Board-Certified Prosthodontists on the Board-Certification Process. Part 2: Preparation and Impact - Behnoush Rashedi, DMD, MS, MSEd,1 Joy Bockstein Abt, DMD,2 and (Journal of Prosthodontics, 2003)
Survey of Recently Board-Certified Prosthodontists on the Board-Certification Process. Part 2: Preparation and Impact